Villainification and Evil in Social Studies Education. (2nd October 2017) - van Kessel, Cathryn; Crowley, Ryan M.
Abstract: Villainification is the process of creating single actors as the faces of systemic harm, with those hyperindividualized villains losing their ordinary characteristics. Like heroification, there is a simplified portrayal of historical actors, but villainification has particularly harmful consequences. We suggest that villainification obscures the way in which evil operates through everyday actions and unquestioned structures because of the focus on the whim of one person. Although it is unfortunate that we do not often see how we can inadvertently help others and make systemic change, it is very disturbing when we fail to see our own part in the suffering of others. This article critiques one-dimensional portrayals of evildoers in K–12 social studies and popular sentiment and offers a framework via the political theory of Hannah Arendt to educate for a sensibility of interconnected responsibility among members of a society instead of blaming one person for systemic harm or diffusing blame into an amorphous entity (e.g., "society").